Distributed democracy : health care governance in Ontario - Doberstein, Carey (Institute of Public Administration of Canada series in public management and governance., 2020)
"The governance of health care in Ontario has long provided many opportunities for citizens and stakeholders to participate, deliberate and influence health care policy and investment decisions. Yet, despite providing more opportunities for citizen deliberation and influence, this book asks, is the system actually democratic? To answer this question, Distributed Democracy advances an original analytical framework to guide an investigation of democracy and accountability relationships in complex policy making environments. Using an analytical framework in the context of health care governance in Ontario from 2004-2019, this book reveals that the popular criticisms of health care governance in Ontario are misplaced, and in fact, misrepresent other problems: the democratic system of local health care governance is often plagued by severed connections among the various layers of deliberation and policy-making. The lessons for the design of truly democratic governance extend beyond the case of health care in Ontario into the numerous policy realms for which citizen and stakeholder participation and deliberation is increasingly practiced."--